2003
DOI: 10.1074/jbc.m307132200
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycan Structures of Pigeon IgG

Abstract: We had shown previously that all major glycoproteins of pigeon egg white contain Gal␣1-4Gal epitopes (Suzuki, N., Khoo, K. H., Chen, H. C., Johnson, J. R., and Lee, Y. C. (2001) J. Biol. Chem. 276, 23221-23229). We now report that Gal␣1-4Gal-bearing glycoproteins are also present in pigeon serum, lymphocytes, and liver, as probed by Western blot with Griffonia simplicifolia-I lectin (specific for terminal ␣-Gal) and anti-P 1 (specific for Gal␣1-4Gal␤1-4GlcNAc␤1-) monoclonal antibody. One of the major glycoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…Pigeon liver was utilized as a source of mRNA to construct the cDNA library for expression cloning, because we detected (Gal␣1-4Gal)-containing glycoproteins in this tissue (12). After the selection using anti-P 1 mAb (specific for Gal␣1-4Gal␤1-4GlcNAc) by cell sorting, the plasmid designated as pcDNA-pigeon␣4GalT(Gal) was isolated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pigeon liver was utilized as a source of mRNA to construct the cDNA library for expression cloning, because we detected (Gal␣1-4Gal)-containing glycoproteins in this tissue (12). After the selection using anti-P 1 mAb (specific for Gal␣1-4Gal␤1-4GlcNAc) by cell sorting, the plasmid designated as pcDNA-pigeon␣4GalT(Gal) was isolated.…”
Section: Resultsmentioning
confidence: 99%
“…Pigeon IgG possesses another unique glycan sequence, Gal␣1-4Gal␤1-4Gal␤1-4GlcNAc, at the nonreducing termini of N-glycans (12). The same sequence is found in O-glycans from the salivary gland mucin of the Chinese swiftlet (13).…”
mentioning
confidence: 91%
“…Additionally, coenzymes or specific chaperons are sometimes also critical for the enzyme activity (58). Whereas pigeon expresses Gal␣1-4Gal glycoproteins not only in egg whites but also in other tissues and f luids (14), no Gal␣1-4Gal has been detected so far in chicken. The apparent absence of Gal␣1-4Gal glycoproteins in entire body of chicken probably ref lects inactivation or absence of the ␣-1,4-GalT gene.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that pigeon (Rock Dove, Columba livia) express Gal␣1-4Gal (galabiose) antigens attached on glycoproteins from egg white (12,13) and serum (14), and analyzed their N-glycan structures (Fig. 1).…”
mentioning
confidence: 99%
“…As glycans can be easily isolated and purified, the ISD and pMS 3 -sequencing approaches were also employed to characterize thoroughly the structures of both native [43,[54][55][56][57][58][59][60] and permethylated glycans [61][62][63][64][65][66], allowing unambiguous discrimination of isobaric species. In ref.…”
Section: Maldi-isd and Ptmsmentioning
confidence: 99%